The impact of intimate partner violence on facial emotion recognition among Korean baby boomers - Hyunsan Cho; June Christoph Kang; Hee-Jin Park; Yoon Hee Park; Yeo Eun Park; Intae Hwang; Hyo Jin Kang (European Journal of Psychotraumatology)
Background: Intimate partner violence (IPV) can have lasting psychological and cognitive effects, potentially impairing facial emotion recognition (FER). This study examines the accuracy of FER among IPV survivors compared to individuals without IPV experience within the Korean baby boomer generation, aged 60-69, exploring the relationship between IPV, post-traumatic stress disorder (PTSD) symptoms, and FER abilities.Objective: To assess whether IPV impacts FER accuracy and intensity and to investigate whether symptoms of PTSD moderate this relationship.Method: The study included 80 participants, with 31 % identified as IPV survivors. A self-administered survey collected information on lifetime experiences of physical, emotional, and sexual abuse, as well as assessments for PTSD symptoms. Participants completed the Korean Montreal Cognitive Assessment (K-MOCA) and performed 70 FER tasks to evaluate accuracy and intensity of facial emotions. Logistic regressions were used to analyse the relationship between IPV, PTSD symptoms, and FER performance.Results: IPV survivors demonstrated 0.64 times lower accuracy in recognizing overall facial emotions, including anger, sadness, surprise, and neutral expressions Additionally, IPV survivors exhibited significantly lower intensity scores for overall facial expressions. Significant interaction terms between IPV and PTSD symptoms indicate that PTSD symptoms moderate the effect of IPV on the FER, as well as neutral and sad facial expressions.Conclusions: IPV can disrupt one's ability to recognize facial emotions, and PTSD symptoms may moderate this impairment. This highlights the potential benefits of assisting IPV survivors with emotion recognition as part of their recovery process, which could enhance both social connections and their safety.